2011
DOI: 10.1039/c0em00258e
|View full text |Cite
|
Sign up to set email alerts
|

Presence and partitioning properties of the flame retardants pentabromotoluene, pentabromoethylbenzene and hexabromobenzene near suspected source zones in Norway

Abstract: The brominated flame retardants (BFRs), pentabromotoluene (PBT), pentabromoethylbenzene (PBEB) and hexabromobenzene (HBB), exhibit physical-chemical properties similar to other persistent organic pollutants, and have been in use as flame retardants for several decades. Data on these BFRs in diverse environmental samples can be found in studies from the 1970s and 1980s, as well as in recent years, though very little in the years in between. Due to a lack of data, the cause for the apparent re-emergence of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 28 publications
2
39
1
Order By: Relevance
“…Comparable levels in eggs from across the Great Lakes suggest common origin of exposure, possibly via atmospheric transport. Arp et al (2011) analysed fish liver, crab and blue mussel samples from three sites in Norway, but HBB could not be identified above the LOQ (0.1 ng/g w.w.).…”
Section: Sewage Sludge and Soilmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparable levels in eggs from across the Great Lakes suggest common origin of exposure, possibly via atmospheric transport. Arp et al (2011) analysed fish liver, crab and blue mussel samples from three sites in Norway, but HBB could not be identified above the LOQ (0.1 ng/g w.w.).…”
Section: Sewage Sludge and Soilmentioning
confidence: 99%
“…The corresponding concentrations at a rural site were 0.10-4.80 pg/m 3 , with an arithmetic mean of 0.75 pg/m 3 . Arp et al (2011) analysed sediment samples outside a metal recycling plant in Drammen (Norway) and found 0.028 ± 0.036 ng/g dry weight (LOD: 0.004, LOQ: 0.01). Körner et al (2011) found PBEB in sewage sludge in Bavaria in concentrations ranging from 0.002 (LOD) to 0.52 ng/g dry weight with a mean of 0.022 ng/g dry weight.…”
Section: From 2005 To 2009 Salamova and Hitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the chemical industry is likely to be a source of PBDEs. Sample 11, collected in Baiyin City, with the highest concentration, [31,32].…”
Section: Distribution Of Pbdes and Pcbs In Urban And Rural Areasmentioning
confidence: 99%